PENGARUH KUALITAS PELAYANAN DAN PENETAPAN HARGA TERHADAP KEPUASAN KONSUMEN PADA RUMAH MAKAN TALAGO BIRU KOTA PEKANBARU - Wiwit Yuliani; Endang Sutrisna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Consumer satisfaction is an important part of the product marketing concept, this is the background of this research. The implementation of good service quality and correct pricing in front of consumers is part of the supporting factors for customer satisfaction. This strategy is determined by the Talago Biru Restaurant in Pekanbaru City. This study aims to determine the effect of service quality and pricing on consumer satisfaction at the Talago Biru Restaurant in Pekanbaru City. The method used in this research is descriptive and quantitative, with the source of the data from this research comes from primary data obtained through the interview process and distributing questionnaires which are then tested statistically through the SPSS program and secondary data using product sales data for the Talago Biru Restaurant Pekanbaru City from 2016-2020. The analytical method used in this research is simple and multiple regression analysis, and through validity and reliability tests. In this study the results obtained are that Service Quality (X1) has a positive and significant effect on Consumer Satisfaction (Y), Pricing (X2) has a positive and significant impact on Consumer Satisfaction (Y), and Service Quality (X1) and Pricing (X2) has a positive and significant effect on Consumer Satisfaction (Y) at the Talago Biru Restaurant in Pekanbaru City. Keywords: Service Quality, Pricing, Customer Satisfaction